A Pathway To Sustainable Development of India by MGNREGA - Dr. Mukesh Chahal (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Sustainable development is a very important concept of the defining ideas of society. Sustainable development is a process to fulfill the needs of the current generation without compromising the fulfillment of the needs of future generations. It's a concept to complete present-time requirements without compromising with future requirements. Several Government programs are running in achieving sustainability of Economy, Agriculture Forest, Income, Health, Gender Equality, and many more. MGNREGA is a flagship program to achieve these goals. MGNREGA is not a program but an act against unemployment. It acts as a growth engine for the sustainable development of the agricultural economy and empowerment of the rural poor including women. This paper highlights the role of the rural development scheme MGNREGA in achieving sustainable development goals. The paper show that MGNREGA is doing well in employing rural people and in the eradication of rural poverty. In addition to this, the scheme has contributed rural people and in the elimination of rural poverty. In addition to this, the scheme has contributed towards gender equality.